Exploring breast cancer preventive lifestyle and social support of Iranian women: a study protocol for a mixed-methods approach - Maryam Khazaee-Pool; Tahereh Pashaei; Leila Jahangiry; Koen Ponnet; Ali Gholami (BMC, 2017)
Abstract Background It is widely accepted that a healthy lifestyle may decrease the probability of developing cancer. This study aimed to describe a study protocol that makes it possible to explore preventive health lifestyles of Iranian women and their received social support for the purpose of developing cultural strategies to increase breast cancer prevention. Methods A mixed-methods study will be accomplished in two sequential parts. First, a cross-sectional study will be conducted in which 2,250 Iranian women are recruited by using a random multistage cluster sampling of 20 health care centers. Structured face-to-face interviews will be conducted to obtain information on the participants' health lifestyle and perceived social support. Data will be analyzed using both multivariate regression and structural equation modeling techniques. Then, a qualitative study will be conducted among employed women using a purposive sampling design. Data will be collected by means of focus groups and semi-structured interviews and will be analyzed using a conventional content analysis approach. The results of the quantitative and qualitative study will be used to develop breast cancer preventive strategies. Discussion Researchers need to acquire knowledge regarding the lifestyle and perceived social support of Iranian women that will foster culturally competent approaches to promote healthy lifestyles to develop breast cancer preventive strategies. Examining breast cancer preventive lifestyles provides valuable information for designing applicable intervention programs for improving women's health.